The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000364827
|View full text |Cite
|
Sign up to set email alerts
|

Different and Shared Brain Volume Abnormalities in Late- and Early-Onset Schizophrenia

Abstract: The differences in clinical characteristics between late- (LOS) and early-onset schizophrenia (EOS) are well documented. However, very little is known about the neural mechanisms underlying these differences. Here, we compared morphometric abnormalities between patients with EOS and those with LOS. A total of 22 patients with LOS, 24 patients with EOS and 41 healthy control subjects were included in this magnetic resonance imaging study. Brain images were analyzed using DARTEL preprocessing for voxel-based mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
(97 reference statements)
1
8
2
Order By: Relevance
“…In contrast to a previous DARTEL-based VBM study [17], we observed decreased GM volumes in the gyrus rectus in patients with schizophrenia. Frontal lobe dysfunction is related to cognitive and affective deficits in patients with schizophrenia [46].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to a previous DARTEL-based VBM study [17], we observed decreased GM volumes in the gyrus rectus in patients with schizophrenia. Frontal lobe dysfunction is related to cognitive and affective deficits in patients with schizophrenia [46].…”
Section: Discussioncontrasting
confidence: 99%
“…One interesting finding of this study is the decreased GM volume of the insula in patients with schizophrenia, which is consistent with the GM volume abnormalities in the insula in schizophrenia observed in previous studies [17,34,35]. Postmortem studies [36,37] have revealed that the reduction of insula volume stems from decreases in the neuronal and glial somal sizes in layer II and III due to poor development and heterogeneity in the upper layers of the insula.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Coincidently, media temporal lobe atrophy was significantly smaller in LOS than in Alzheimer's disease [83]. Contrary to observations in LOS, disease duration appeared positively associated with a reduction in the temporal pole in AOS [84]. Additionally, even though the pattern of atrophy described by Rabins et al [73] was comparable to that found in AOS, the main changes were located in the right hemisphere NEUROPSYCHOLOGY AND NEUROBIOLOGY OF LOS AND VLOSLP 24 whereas AOS is suggested to show more left hemisphere pathology.…”
Section: Volumetric Brain Changes: Atrophy And/or Dysgenesis An Incrcontrasting
confidence: 68%